2019
DOI: 10.1002/psp4.12414
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically‐Based Pharmacokinetic Modeling of Fluconazole Using Plasma and Cerebrospinal Fluid Samples From Preterm and Term Infants

Abstract: Fluconazole is used to treat hematogenous Candida meningoencephalitis in preterm and term infants. To characterize plasma and central nervous system exposure, an adult fluconazole physiologically‐based pharmacokinetic (PBPK) model was scaled to infants, accounting for age dependencies in glomerular filtration and metabolism. The model was optimized using 760 plasma samples from 166 infants (median postmenstrual age (range) 28 weeks (24–50)) and 27 cerebrospinal fluid ( CSF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…This drug diffuses in all body tissues where reaches effective concentration, and tissue-plasma partition coefficient is 2.03 [3]. Penetration into cerebrospinal fluid is good [38,39] and successfully cured meningitis caused fungemia [40,41], and is the drug of choice for treatment of meningitis caused by Coccidioidal meningitis [2]. Fluconazole also migrates into breast-milk in significant amounts, the estimated relative infant dose is 17% of the maternal dose, and drug half-life is 30 hours in breast-milk, thus it is longer than that of found in healthy volunteers [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This drug diffuses in all body tissues where reaches effective concentration, and tissue-plasma partition coefficient is 2.03 [3]. Penetration into cerebrospinal fluid is good [38,39] and successfully cured meningitis caused fungemia [40,41], and is the drug of choice for treatment of meningitis caused by Coccidioidal meningitis [2]. Fluconazole also migrates into breast-milk in significant amounts, the estimated relative infant dose is 17% of the maternal dose, and drug half-life is 30 hours in breast-milk, thus it is longer than that of found in healthy volunteers [42].…”
Section: Discussionmentioning
confidence: 99%
“…Gerhart et al [38] characterized fluconazole exposure in plasma of 22 infants with mean postmenstrual age of 28 weeks (range, 24 to 50), and in cerebrospinal fluid of 27 infants with a mean postmenstrual age of 28 weeks (range, 24 to 33). Cerebrospinal fluid concentration ranged from 0.1 to 9.6 µg/ml and was obtained 3.3 to 219 hours from the last dose.…”
Section: Fluconazole Penetration Into Cerebrospinal Fluid Of Infants and Childrenmentioning
confidence: 99%
“…There were four preterm infants with PK data who received sildenafil with fluconazole. We comodeled sildenafil with fluconazole in preterm infants leveraging a previously published fluconazole PBPK model in adults and infants, including renal clearance and uridine 5′‐disphospho‐glucuronosyltransferase family 2 member B7 (UGT2B7) metabolism 32,35 . Only the indication (prophylaxis vs. treatment) for fluconazole was recorded for these preterm infants.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty studies investigating the in vivo phase II metabolism were identified ( Windorfer and Pringsheim, 1977 ; Mulhall et al, 1983a ; Choonara et al, 1989 ; Hartley et al, 1993 , 1994 ; H et al, 1993; Reiter and Stiles, 1993 ; Brammer and Coates, 1994 ; Sato et al, 1997 ; Wenzl et al, 1998 ; Wade et al, 2008 , 2009 ; Knibbe et al, 2009 ; Krekels et al, 2015 ; Mahmood, 2015 ; Auriti et al, 2016 ; Cook et al, 2016 ; Flint et al, 2017 ; MF et al, 2017 ; Leroux et al, 2018 ; Gerhart et al, 2019 ). A large heterogenitet was found and several substrates were used and included chloramphenicol, morphine, fluconazole, lorazepam, micafungin, paracetamol, and mefenamic acid.…”
Section: Exploring the Available Data On Premature Neonates: An Examp...mentioning
confidence: 99%